Review of Pyrochroidae (Coleoptera: Tenebrionoidea) from Mêdog, China, with descriptions of two new species - Gao, Qi; Yang, Xin-Mei; Young, Daniel K.; Pan, Zhao-Hui; Pan, Zhao (Zootaxa, 2026)
Pyrochroidae Latreille, 1806 exhibits a broad distribution spanning all major regions of the world except Antarctica. In the present comprehensive review of the family from Mêdog County, Xizang, five species representing three genera within two subfamilies are recorded. Among them, two new Pseudopyrochroa species, P. concava Gao, Young & Z. Pan, sp. nov. and P. nyingchica Gao, Young & Z. Pan, sp. nov., were discovered and are described herein. Agnathus secundus Jelínek & Kubáň, 2009 and P. antennalis (Blair, 1912) are recorded for the first time in the county. Dorsal habitus and morphological details relating to the four species above are illustrated. A key to the five pyrochroid species of Mêdog is provided.